Role Multimedia Interactive in Learning PPKn in Elementary School - Syahputri, Hemalia (International Journal of Students Education, 2024)
Education is one of the aspects that determines the intelligence of a nation, so educational institutions and teachers are needed to carry out creative and innovative learning. To provide understanding to students can be done through the use of learning media. One of the learning media that can be used is interactive learning media by utilizing information and communication technology or using multimedia. The purpose of this study is to determine the role of interactive media and its application in PPKn learning in elementary schools. Interactive learning media can be used in every subject, one of which is in PPKn lessons. PPKn lessons aim to form the character of good citizens, namely those who know, want and are aware of their rights and obligations. By using qualitative research methods obtained based on the results of interviews with researchers with resource persons, namely teachers, and literature reviews by looking at experts who have researched this research before. With the presence of interactive multimedia learning become Far more interesting, especially in elementary school children and students understand the learning more easily because students learn happily. Intraltof multimedia applied in elementary school PPKn learning by teachers greatly influences the achievement of learning. Interactive multimedia greatly supports student learning activities effectively. The development of interactive multimedia must continue to be carried out, especially in PPKn learning for the sake of effective learning. Difficult material can be conveyed easily because of multimedia.